Apontamentos sobre a publicação de história da vida privada em Portugal: Entrevista com José Mattoso - Mattoso, José; Teodoro, Leandro Alves [UNESP] (FapUNIFESP (SciELO), 2012)
Interview given to Leandro Alves by José Teodoro Mattoso, professor at the NewUniversity of Lisbon, a renowned medievalist and author of several important works on Portuguese historiography. He recently coordinated the publication of the History of private life in Portugal, a work encompassing the Middle Ages through to the present day, addressing the field of study of behaviors and mentalities, which until then had barely been touched upon by Portuguese historians. Seeking to outline a historiographical perspective regarding the use of the history of mentalities in Portugal, a series of questions were prepared to put to Mattoso about the interests that led him to organize such a collection of unpublished essays.
Notes on the publication of the history of private life in Portugal: An interview with José Mattoso
Keywords: History of private life; José Mattoso (1933); New history; Portugal; Portuguese historiography